Pengembangan Handout Fisika Berbasis CORE (Connecting, Organizing, Reflecting and Extending) untuk Meningkatkan Higher Order Thinking Skills pada Peserta Didik SMA - Nurul Fatikhakh; Arif Maftukhin; Siska Desy Fatmaryanti (Radiasi : Jurnal Berkala Pendidikan Fisika, 2018)
Abstract – This study aims to: (1) Determine the feasibility of developing a CORE-based Physics handout. (2) Determine students' responses to the use of CORE-based Physics handouts. (3) Knowing the increase in students' HOTS after the use of a CORE-based Physics handout in the learning process. The type of research carried out is research and development, using the ADDIE development model. The stages include, analyze, design, development, implementation and evaluation. Product trials were conducted for students of class X MIPA program in SMA Negeri 1 Pejagoan. To get the interpretation of the data obtained, data analysis is performed by changing the score from a scale of four into a percentage. Then calculate the value of the Percentage Agreement (PA) to determine the reliability of the implementation of learning. As well as normalized gain to determine the increase in HOTS of students from the results of pre-test and post-test. The results of the validation test, the average of the three validators was 3.48. So that this CORE-based Physics handout is in the "good" category and is appropriate for use in learning Physics. Student response test produces a score of 2.96 with the category "Enough". This CORE Based Physics Handout can improve high order thinking skills on the cognitive aspects of high school students in class X SMA N 1 Pejagoan with a normalized gain of 0.6981 in the "Medium" category. These results indicate that the CORE Based Physics Handout can be an alternative teaching material for high school physics learning.